Religionization and world obfuscation: the display of computers, robots, and big data-based applications in museums - Prohl, Inken (Religion, 2025)
This article examines how museums and exhibitions present the use and impact of AI and robotics, focusing on the narratives they construct around technological promise and risk. Case studies include the Zukunftsmuseum in Nuremberg, the Futurium in Berlin, and the traveling exhibition "Hello Robot". Additional insights are derived from institutions such as the Ars Electronica Center (Linz), the Deutsches Museum (Bonn/Munich), and the Miraikan in Tokyo. Based on discourse analysis and participant observation, the study draws on approaches from Material Religion and Cultural Sociology. It explores curatorial agendas, artifact selection, and modes of presentation, identifying glorification, mystification, and aestheticization as key features in how AI is exhibited. These strategies contribute, as will be shown, to perceiving AI as a formation analogous to religion while simultaneously obscuring critical dimensions. The conclusion highlights how, by blending technological reality with speculative fiction, such exhibitions risk promoting a selctive, obfuscating vision of the future.
Gesehen am 01.07.2025